2019
DOI: 10.1039/c9fo00399a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of traditional Chinese medicine treatment on chronic unpredictable mild stress-induced depression-like behaviors: intestinal microbiota and gut microbiome function

Abstract: Gut microbiota dysbiosis is a recognized contributing factor to many noncommunicable diseases, but more evidence is still needed to illustrate its causative impact on mental and brain health disorders and mechanism(s) for targeted mitigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 65 publications
7
32
0
Order By: Relevance
“…Ruminococcus is a type of pathogenic bacteria. Studies have reported that traditional Chinese medicine treatments and marketed antidepressants can reduce the abundance of Ruminococcus in the intestine (Lukic et al, 2019;Qu et al, 2019). Consistent with the results of a CUMS rat study, the level of Ruminococcus in psychotic patients also increased (Clark and Mach, 2016;Zhuang et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Ruminococcus is a type of pathogenic bacteria. Studies have reported that traditional Chinese medicine treatments and marketed antidepressants can reduce the abundance of Ruminococcus in the intestine (Lukic et al, 2019;Qu et al, 2019). Consistent with the results of a CUMS rat study, the level of Ruminococcus in psychotic patients also increased (Clark and Mach, 2016;Zhuang et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, no statistically signi cant modi cation of the α-diversity was observed in CUMS mice by comparison to controls, indicating that the within-community diversity was not altered by this model of chronic stress. Although these results are in agreement with other studies using variants of the rodent CUMS model [9,29], they are discrepant when compared to other works describing a decrease of αdiversity [14,16,33,34]. Such differences could be explained by variation in the CUMS protocols (species, strains, age, gender and feeding conditions of rodents, type of stressors, duration of exposure to individual stress), the origin of the samples (fecal or intraluminal), or protocol parameters (DNA extraction method, PCR parameters) [3].…”
Section: Discussionsupporting
confidence: 93%
“…However, signi cant change in intracaecal global β-diversity was observed after CUMS treatment. Indeed, an important increase of the Firmicutes/Bacteroidetes ratio was observed in CUMS mice, consistently with other reports using variants of the rodent CUMS model [9,16,29,33]. Within the Bacteroidetes phylum, we observed a decrease of Porphyromonadaceae that has already been noted with other chronic stress such as restraint stress [36] and multifactorial model of early-life adversity [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the neurobiology of depression is accompanied by oxidative stress in the brain and throughout the organism (Silva et al, 2016). In terms of the chronic unpredictable mild stress (CUMS)-induced depression, traditional Chinese medicine has been applied for controlling CUMS-induced depression-like behaviors (Qu et al, 2019). Therefore, it is necessary to explore the specific mechanism of traditional Chinese medicine in CUMS-induced depression-like behaviors.…”
Section: Introductionmentioning
confidence: 99%